2013
DOI: 10.12660/rbfin.v11n3.2013.7434
|View full text |Cite
|
Sign up to set email alerts
|

Comunalidades na Liquidez – Evidências e Comportamento Intradiário para o Mercado Brasileiro

Abstract: The objective of this work is to study the intraday dynamics of liquidity in the Brazilian stock exchange from the perspective of co-movements (or commonalities). In the study we argue that this common factor in the liquidity of the stocks is affected by the intraday patterns related to microstructure effects in the market. Using a high frequency database, such a hypothesis is investigated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Both in the international and national literature, many are the studies that seek to survey and identify the sources of demand-side explanation of commonality. For example, the studies of Karolyi et al (2012), Victor et al (2013), Milani, Bender, Ceretta, Vieira, and Coronel (2014), and Silveira et al (2014) documented the existence of commonality in liquidity for the Brazilian stock market and, according to demand-side explanations, identified that commonality emerges from the herding behavior of institutional investors (Karolyi et al, 2012;Silveira et al, 2014) or from the participant adjustment to shared information (Victor et al, 2013).…”
Section: Demand-sidementioning
confidence: 99%
See 2 more Smart Citations
“…Both in the international and national literature, many are the studies that seek to survey and identify the sources of demand-side explanation of commonality. For example, the studies of Karolyi et al (2012), Victor et al (2013), Milani, Bender, Ceretta, Vieira, and Coronel (2014), and Silveira et al (2014) documented the existence of commonality in liquidity for the Brazilian stock market and, according to demand-side explanations, identified that commonality emerges from the herding behavior of institutional investors (Karolyi et al, 2012;Silveira et al, 2014) or from the participant adjustment to shared information (Victor et al, 2013).…”
Section: Demand-sidementioning
confidence: 99%
“…Evidence from international studies suggests that commonality may derive from the behavior of institutional investors (Koch et al, 2016;Narayan et al, 2015). In turn, studies regarding the Brazilian stock market used demand-side explanations to support their findings, that is, they argued that commonality derives from investor behavior, whereby commonality results from herding (Silveira et al, 2014) or from participant adjustment to shared information (Victor et al, 2013).…”
Section: Measuring Commonality In Liquiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Although most studies using intraday data addressed risk and return topics, this type of data has also been used in the analysis of other subjects such as market liquidity and its commonalities (Victor et al, 2013, Silveira et al, 2014, Casarin, 2011, Marquezin and De Mattos, 2014, Perlin, 2013, bid-ask spreads/order book analysis (Cajueiro and Tabak, 2007, Maluf and Otiniano, 2014, asymmetric information and corporate governance (Barbedo et al, 2007, Neto et al, 2012, Martins and Paulo, 2014, computation and algorithm programming (Silva et al, 2014, high frequency data distribution (Horta and Ziegelmann, 2011, Cortines and Riera, 2007, Block et al, 2015 and other research topics in Finance (Taufemback and Da Silva, 2011, Caetano and Yoneyama, 2007, Biage et al, 2010, Perlin et al, 2014. Table 1 summarizes recent high frequency data studies in Brazil.…”
Section: Literature Reviewmentioning
confidence: 99%
“…See also Mussa (2012) and references therein. Victor et al (2013) investigate the existence of a common factor that governs the liquidity of every stock in the BM&FBovespa. Perlin (2013) conducts a very interesting analysis of the entry of liquidity agents in the BM&FBovespa.…”
Section: Introductionmentioning
confidence: 99%